2018
DOI: 10.1002/tal.1481
|View full text |Cite
|
Sign up to set email alerts
|

Load resistance and hysteretic response of rhombic grid hyperboloid‐latticed shell subjected to combined vertical and horizontal loads

Abstract: A new type of rhombic grid hyperboloid-latticed shell (RGHLS) being investigated in this study is only formed by major and secondary inclined columns without any circumferential hoop members. This intends to achieve more transparency for architectural effect by neglecting its circumferential hoop members and lateral braces in radial direction of the RGHLS, and meanwhile, the RGHLS is expected to experience a significant strength reduction. This paper numerically investigates the load resistance and hysteretic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Lightweight materials with low Young's modulus, such as timber and fiber‐reinforced polymer, are commonly used in such structures to achieve large deformations. Gridshell structures are advantageous because of their high structural efficiency; hence, several innovative variations have been proposed in the past decades . However, unlike conventional gridshells, the members in elastic gridshells are mainly stressed by bending moments instead of axial forces.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight materials with low Young's modulus, such as timber and fiber‐reinforced polymer, are commonly used in such structures to achieve large deformations. Gridshell structures are advantageous because of their high structural efficiency; hence, several innovative variations have been proposed in the past decades . However, unlike conventional gridshells, the members in elastic gridshells are mainly stressed by bending moments instead of axial forces.…”
Section: Introductionmentioning
confidence: 99%
“…The other performances of the fabricated reticulated shells, such as fire resistance and collapse resistance, were also investigated. [13][14][15][16] Through analysis, it is found that scholars only analyzed the influence of joint stiffness on the overall stability and bearing capacity of reticulated shells, but no one has noticed that while improving the joint stiffness, the number of semirigid joints in reticulated shells can be reduced, and semirigid joints can be placed in the middle of the members to realize modular assembly of the reticulated shell.…”
mentioning
confidence: 99%